WOUND HEALING MEDICINAL PLANTS-AN OVERVIEW - R.DEVIKA, (International Journal of Pharma and Bio Sciences, 2015)
From the historic era, plants have been a proved to be an excellent source of food, shelder and medicine for various ailments of mankind and animals. Nowadays, research has been focussed on the utility of the plant sources as an alternative medicine as they are less cost with fewer side effects. Wound healing is one of the major process which involves various stages with multiple components involvements. The present review articles reveals the importance of the stages of wound healing and the various traditional methods involved with medicinal plants. This emphazises the value of plant products used in various ailments and the methods involved for wound healing processes.